2004
DOI: 10.1038/ncb1193
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of myocardial patterning in cardiac development by Sema6D reverse signalling

Abstract: Cardiac chamber formation involves dynamic changes in myocardial organization, including trabeculation and expansion of the compact layer. The positional cues that regulate myocardial patterning, however, remain unclear. Through ligation of the Plexin-A1 receptor, the transmembrane-type semaphorin Sema6D regulates endocardial cell migration. Here, we demonstrate that knockdown of either Sema6D or Plexin-A1 leads to the generation of a small, thin ventricular compact layer and to defective trabeculation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(172 citation statements)
references
References 21 publications
5
167
0
Order By: Relevance
“…Concomitantly, we also observed a late-phase disruption of CrkL phosphorylation with Sema6D-Ig treatment. Previous studies have reported that Sema6D can activate Abl kinase and that within T cells, Abl regulates phosphorylation of CrkL and LAT but not CD3 (16,20). Given that Sema6D surface protein expression is not enhanced until the late phases of activation, it appears possible that the late-phase inhibition of pLAT may derive directly from a defect in Sema6D signaling by Abl kinase activity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Concomitantly, we also observed a late-phase disruption of CrkL phosphorylation with Sema6D-Ig treatment. Previous studies have reported that Sema6D can activate Abl kinase and that within T cells, Abl regulates phosphorylation of CrkL and LAT but not CD3 (16,20). Given that Sema6D surface protein expression is not enhanced until the late phases of activation, it appears possible that the late-phase inhibition of pLAT may derive directly from a defect in Sema6D signaling by Abl kinase activity.…”
Section: Discussionmentioning
confidence: 93%
“…These effects of Sema6D-Ig on cell signaling may be explained by two recent reports. The first identified that Sema6D can activate Abl kinase within heart tissue (16). The second demonstrated that within T cells, Abl kinase regulates phosphorylation of LAT but not CD3 (20).…”
Section: Inhibition Of Sema6d Reduces a Late Phase Of T Cell Activatimentioning
confidence: 99%
See 1 more Smart Citation
“…BCR-ABL tyrosine kinase inhibitor, STI571 (imatinib mesylate), was kindly gifted by Novartis Pharmaceuticals (Basel, Switzerland). Expression vectors for p190/ p210BCR-ABL, ABL, STAP-2 and their mutants were described previously Toyofuku et al, 2004;Sekine et al, 2005;Tokunaga et al, 2010). Expression vectors for Myc-tagged-BCR was generated by PCR methods and sequenced (primer sequences are available upon request).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Recent studies in chick embryos have shown that Sema6D is a ligand for plexin-A1 and that their interaction is important for mediating the expansion of the cardiac primordium. 74 However, at later stages of heart development plexin-A1 acts as a ligand and Sema6D as its receptor. 25 Upon plexin-A1 binding Abl kinase is recruited to the cytoplasmic tail of Sema6D and activated, resulting in phosphorylation of enabled and dissociation from Sema6D.…”
Section: Classmentioning
confidence: 99%